Dampak Oligopoli Dan Industri Modern Terhadap Masyarakat - Riska Intan Pramitaning Tyas; Muhammad Yasin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Oligopoly is a form of imperfect market competition where the supply of a product is controlled by a number of companies. In general the number of companies is more than two but less than ten. Each company decides its own policy and all company actions as price changes will be taken into account by other companies, because every company in the market believes in the policy of a company. This business will affect the income and profits of other businesses. In an oligopoly market, each company positions itself as part of a market game so that its profit base is based on the behavior of its competitors. So all promotional efforts, advertising, new product introductions, price changes, etc. This is done with the aim of luring consumers away from competitors. The main cause of this oligopoly is the successful management of business operations to achieve economies of scale which leads to the effectiveness and success of sales promotions in the long term, because it will increase market share. Oligopoly activities are often with the aim of inhibiting potential business participation in the market. More than that, it also aims to enjoy normal profits below the maximum by setting a limited selling price so that price competition between business actors who carry out an oligopoly does not exist.